Biosynthetic hydrogels—Studies on chemical and physical characteristics on long‐term cellular response for tissue engineering. Issue 7 (14th August 2013) - Thankam, Finosh Gnanaprakasam; Muthu, Jayabalan
Abstract Biosynthetic hydrogels can meet the drawbacks caused by natural and synthetic ones for biomedical applications. In the current article we present a novel biosynthetic alginate ‐ poly(propylene fumarate) copolymer based chemically crosslinked hydrogel scaffolds for cardiac tissue engineering applications. Partially crosslinked PA hydrogel and fully cross linked PA‐A hydrogel scaffolds were prepared. The influence of chemical and physical (morphology and architecture of hydrogel) characteristics on the long term cellular response was studied. Both these hydrogels were cytocompatible and showed no genotoxicity upon contact with fibroblast cells. Both PA and PA‐A were able to resist deleterious effects of reactive oxygen species and sustain the viability of L929 cells. The hydrogel incubated oxidative stress induced cells were capable of maintaining the intra cellular reduced glutathione (GSH) expression to the normal level confirmed their protective effect. Relatively the PA hydrogel was found to be unstable in the cell culture medium. The PA‐A hydrogel was able to withstand appreciable cyclic stretching. The cyclic stretching introduced complex macro and microarchitectural features with interconnected pores and more structured bound water which would provide long‐term viability of around 250% after the 24th day of culture. All these qualities make PA‐A hydrogel form a potent candidate for cardiac tissue engineering. © 2013 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 102A: 2238–2247, 2014.